Games Decisions and Industrial Organization - Shubik, M. (Management Science, 1960)
A survey of the current relationship between the many different problem areas investigated by means of Game Theory and the study of Industrial Organization is presented. Several examples are provided to illustrate the nature and relevance of work on (1) two-person constant-sum games; (2) the extensive form of a game; (3) theories of solution for n-person games; (4) theories of solutions for games against nature; and (5) theories of solution for dynamic games. The nature and state of the current applications of game theory to organizational problems and to parts of the behavorial sciences are summarized.